2011
DOI: 10.1029/2011ja016901
|View full text |Cite
|
Sign up to set email alerts
|

Continuous ground-based multiwavelength airglow measurements

Abstract: [1] A new spectrograph instrument, called the Continuous High-resolution Instrument for Multiwavelength Echelle Spectroscopy (CHIMES), has been designed to make simultaneous and spatially overlapping ground-based measurements of the green line and red line airglow emissions (5577 Å and 6300 Å) continuously, 24 hours-a-day. The spectrograph uses a 50 mm long, 50 mm wide slit, and varies the exposure time at different times of day (daytime, twilight, and nighttime), from 2 s in daytime to 10 min at night. It uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As it can be seen, there is a Fraunhofer feature in the immediate vicinity of the 297.2 nm, which is not known to contain any emission or absorption, and so it is used to estimate the contribution of scattering in the emission region (of 297.2 nm), assuming that the magnitudes of the scattering in such closely separated spectral regions are the same. It has been shown that this method successfully accounts for removing the scattering contribution when deriving optical emissions during daytime that are buried in the strong solar background continuum for visible daytime airglow and auroral emissions [e.g., Pallamraju and Chakrabarti , ; Marshall et al ., ; Pallamraju et al ., ]. OI 297.2 nm emission intensities are obtained for different view directions as a function of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it can be seen, there is a Fraunhofer feature in the immediate vicinity of the 297.2 nm, which is not known to contain any emission or absorption, and so it is used to estimate the contribution of scattering in the emission region (of 297.2 nm), assuming that the magnitudes of the scattering in such closely separated spectral regions are the same. It has been shown that this method successfully accounts for removing the scattering contribution when deriving optical emissions during daytime that are buried in the strong solar background continuum for visible daytime airglow and auroral emissions [e.g., Pallamraju and Chakrabarti , ; Marshall et al ., ; Pallamraju et al ., ]. OI 297.2 nm emission intensities are obtained for different view directions as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…The method of greenline emission extraction had been discussed in detail earlier [ Marshall et al ., ; Pallamraju et al ., ]. For the observations reported here, the slit of MISE was aligned along the magnetic meridian.…”
Section: Resultsmentioning
confidence: 99%
“…It is a challenge to make ground-based measurements of thermospheric dayglow emission intensities as these are buried in the strong solar scattered background continuum. However, innovations in the recent past have enabled unambiguous measurements of daytime optical emissions from the ground [e.g., Narayanan et al, 1989;Sridharan et al, 1993Sridharan et al, , 1998Chakrabarti et al, 2001;Pallamraju et al, 2002Pallamraju et al, , 2013Gerrard and Meriwether, 2011;Marshall et al, 2011].…”
Section: Measurement Techniquementioning
confidence: 99%
“…Clouds generally hinder the ground-based detection of OH * airglow emissions, sunlight significantly reduces the detected airglow intensity. For other species such as oxygen airglow (green line: 557.7 nm centred at night around a height of 97 ± 3 km (Wolff, 1966), red line: 630 nm centred around 300 km (Danilov, 1962), which is relatively broad compared to the other airglow layers mentioned here), it could be shown that ground-based daytime measurements are possible based on different instruments (see Marshall et al, 2011;Pallamraju et al, 2002 and citations therein). For OH * airglow, at least to our knowledge, only one technique is published using a multiwavelength photometer (Sridharan et al, 1998).…”
Section: Discussionmentioning
confidence: 81%